Why do we consume as we do? The case of ICT spending in the Spanish market - Aurora Ruíz-Rúa; Fernando Fernández-Bonilla; Covadonga Gijón (International Telecommunications Society (ITS), 2023)
This paper presents the research on the last fourteen years household spending patterns on information and communication technology (ICT) and the associated use of digital services due to socioeconomic variables. We found that over the 14 years covered by the research, there is a gender gap in ICT spending that extends beyond the pandemic COVID-10 to the present day, as well as an income gap. Women spend less on ICT than men, although according to the most recent data, this difference is no longer significant. Furthermore, the expected income gap should not be ignored, as fewer resources invested in telecommunications means less ability to move up the labour market, and this may be another way of damaging the social ladder.
Keywords: 330; ICT; online literacy; consumers; survey data; econometric models; behavioral economics